GeOC User Guide. - Fradi, Fajr; Jaspe, Jim; Ayyash, Bashar; Le, Quang Bao; Bonaiuti, Enrico; Cullhaj, Megi; Lettieri, Federico; Graziano, Valerio (2017)
This is the user guide of the The Global Geo-Informatics Options by Context (GeOC) tool. The Global Geo-informatics Context and Options (GeCO) is a new web-based GIS tool that enables its users to define, monitor, assess and co-create knowledge and learning on relevant Sustainable Land Management (SLM) options that match the social-ecological context at global, regional and national scales